2019
DOI: 10.1002/mgg3.610
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐phenotype correlations and BH4 estimated responsiveness in patients with phenylketonuria from Rio de Janeiro, Southeast Brazil

Abstract: Background Genetic heterogeneity and compound heterozygosis give rise to a continuous spectrum of phenylalanine hydroxylase deficiency and metabolic phenotypes in phenylketonuria (PKU). The most used parameters for evaluating phenotype in PKU are pretreatment phenylalanine (Phe) levels, tolerance for dietary Phe, and Phe overloading test. Phenotype can vary from a “classic” (severe) form to mild hyperphenylalaninemia, which does not require dietary treatment. A subset of patients is responsive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…As observed by others, discordant predictions were found mainly in the moderate group or the border of categories assigned. [21,23] Intrinsic conformational changes in the mutated enzymes driven by interallelic interaction may explain to some degree the inaccurate prediction in this group of patients [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…As observed by others, discordant predictions were found mainly in the moderate group or the border of categories assigned. [21,23] Intrinsic conformational changes in the mutated enzymes driven by interallelic interaction may explain to some degree the inaccurate prediction in this group of patients [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary restriction of phenylalanine remains the mainstay of treatment but PKU is an active area of research and new treatment options are emerging that might reduce the burden of the difficult and restrictive diet on patients and their families (Enacán et al, 2019; Giovannini et al, 2012; Harding & Blau, 2010; Sumaily & Mujamammi, 2017; Walter et al, 2002). On the contrary, patients with gene variants that determine a high residual enzyme activity (those with the mildest metabolic phenotypes) have a higher probability of responding to BH4 (Bueno et al, 2013; Michals‐Matalon et al, 2007; Rivera et al, 2011; Staudigl et al, 2011; Vieira Neto et al, 2019). In this regard, patients with a genotype known to be non‐BH4‐responsive should not undergo BH4 testing, while patients with a genotype with BH4‐responsive variations may directly proceed to a treatment trial rather than a BH4 loading test.…”
Section: Discussionmentioning
confidence: 99%
“…The encoded PAH enzyme converts phenylalanine to tyrosine 2 . Neto et al (2019) found that mutations in the PAH gene can include deletion with frame shift, in-frame deletion, large deletion, missesnse, nonsense, and splicing sites 5 (Table 2) (Wang et al, 2017). There have been identified PAH 1101 variants in PAHvdb Database; 6 about 50% are missense mutations.…”
Section: The Pah Genementioning
confidence: 99%
“…Reduction of PAH leads to increase of phenylalanine in blood and brain (Van Wegberg, 2017). Four classification of PKU 4 (Neto et al, 2019) severe (higher than 1,200 µM), moderate (between 900 and 1,200 µM), mild (between 600 and 900 µM), and non-PKU mild (lower than 600 µM) (Neto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%